Efficiency tests for screening production strategies in a lettuce-juvenile tilapia aquaponics system in Brazil - Flores, Roberto Manolio Valladão; Preckel, Paul V.; Quagrainie, Kwamena; Widmar, Nicole Olynk; Silva, Laura [UNESP]; da Costa, Jesaias Ismael [UNESP]; Pinho, Sara M. [UNESP]; Portella, Maria Célia [UNESP]; Branco, Thais Castelo; Filho, Manoel Xavier Pedroza (Springer Nature, 2022)
This article assesses strategies for managing the economic returns to an aquaponics production system with joint products of lettuce and tilapia. Experimental data from Brazil that varied fish stocking density and the fish feeding rate are analyzed using nonparametric efficiency testing methods to identify potentially profitable technologies and their sensitivities to prices of inputs and outputs. Plants and fish production are symbiotic in an aquaponics system, with fish waste providing nutrients for plant growth and plants helping maintain water quality for the fish via filtration. The optimal input/output mix among alternatives is identified, and sensitivity analysis is used to assess the price ranges around recent market conditions (0.18 R$/tilapia fingerling, 2.8 R$/kg for fish feed, 20 R$/kg for juvenile fish, and 1.57 R$/kg for lettuce) over which that technology choice remains optimal. The configuration of production controls is robust to price changes. Results show that at low fish stocking densities (100 fish/m3), the effluent in the water provides insufficient nutrients to plants. In addition, early lettuce harvests (before 26 days) are generally less efficient than treatments that allow more time for plant growth. Sensitivity analysis indicates that the optimality of the identified configuration of production controls is robust with respect to input and output prices.
Keywords: Aquaponics; Feeding rate; Nonparametric efficiency analysis; Stocking density; Tilapia and lettuce production